Enhancing underwater object detection through water artifact removal and using ensemble transfer learning - Saikat, Nayem Hossain; Jahan, Sarowar; Abrar, Fahim; Rahman, Md. Motaqabbir; Rahman, Md. Ashikur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.